2022
DOI: 10.3389/fmicb.2022.894283
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Gut Microbiota in Breast Cancer Occurrence and Bone Metastasis

Abstract: Breast cancer is the most common cancer in women and the second most common cancer overall. Although advancements in the early diagnosis and therapy of breast cancer have occurred in recent years, the prognosis of breast cancer bone metastasis remains poor and this type of cancer is rarely cured. The gut microbiota is indispensable for internal homeostasis and regulates various biological processes. Understanding the gut microbiota profiles in normal controls (NCs), breast cancer patients with no metastasis (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
1
16
1
Order By: Relevance
“…Consistent with this, the gut microbiota is different between individuals with cancer, including breast cancer, and those who are cancer free 97,98 . A recent study reported a lack of Megamonas and Akkermansia in the gut microbiota in metastatic breast cancer patients, compared with non‐metastatic patients 99 . In the same study, it was also reported that the gut microbiota composition in metastatic breast cancer patients was predictive of changes in lipid transportation and metabolism and folate biosynthesis 99 .…”
Section: Gut Microbiota and Breast Cancermentioning
confidence: 81%
See 2 more Smart Citations
“…Consistent with this, the gut microbiota is different between individuals with cancer, including breast cancer, and those who are cancer free 97,98 . A recent study reported a lack of Megamonas and Akkermansia in the gut microbiota in metastatic breast cancer patients, compared with non‐metastatic patients 99 . In the same study, it was also reported that the gut microbiota composition in metastatic breast cancer patients was predictive of changes in lipid transportation and metabolism and folate biosynthesis 99 .…”
Section: Gut Microbiota and Breast Cancermentioning
confidence: 81%
“… 99 In the same study, it was also reported that the gut microbiota composition in metastatic breast cancer patients was predictive of changes in lipid transportation and metabolism and folate biosynthesis. 99 However, these differences mostly reflect cancer‐induced changes in the microbiota rather than changes, which cause cancer.…”
Section: Gut Microbiota and Breast Cancermentioning
confidence: 93%
See 1 more Smart Citation
“…Wenhui and colleagues [ 166 ] compared the GM profiles from breast cancer patients with no metastasis (w/oBMs) , breast cancer patients with bone metastasis (BMs) and control individuals (Cs). They found that the community diversity was the lowest in patients with BMs.…”
Section: The Relationship Between Gut Microbiome and Bone-related Dis...mentioning
confidence: 99%
“…Cultivable bacteria with broad microbial viability have been found in mammary tumor tissues, and depletion of intratumor bacteria reduces breast cancer metastasis ( 11 13 ). Moreover, the complex interaction of microbiota and steroid hormone has a influence on bone metastasis of breast cancer ( 14 ).…”
Section: Introductionmentioning
confidence: 99%